Relationship Between Self Efficacy and Anxiety in Final Adolescents Ahead of Final School Exams - Kurnia, Ai; Dolifah, Dewi; Yuliana, Delli (Poltekkes Kemenkes Jakarta III, 2025)
In Indonesia, an estimated 14 million people or 6.1% of the population aged 15 years and over experience increased anxiety. The profile of adolescents in 2021, as many as 46 million adolescents in Indonesia or 17% of the total population of this country which is 270,203,917 people aged between 10 and 19 years. Self-efficacy concerns an individual's belief in their ability to carry out tasks or actions needed to achieve certain results. Low self-efficacy will cause anxiety, especially when facing exams. The purpose of this study was to determine the relationship between self efficacy regarding magnitude, strength, and generality with anxiety in late adolescents approaching the final exam at SMAN Situraja. This study uses quantitative research methodology and Spearman rho correlational research design, with a sample of 80 respondents. The sampling technique used was Custer random sampling by applying inclusion and exclusion criteria, The data collection instrument used quantitative cross sectional with IBM SPSS Statistics. The results of this study stated that most adolescents have high self-efficacy with normal anxiety as many as 46 people (57.5%). Based on the statistical test, the significance value of self-efficacy with anxiety in late adolescents using Spearman rho produced a p value <0.1. How important it is to support teens in gaining self-efficacy so they can manage the stress of tests. This can involve giving pupils techniques to increase their self-confidence, fostering supportive situations, and giving them positive reinforcement. Supporting self-belief can play a significant role in fostering mental health and academic achievement.